Genetic control of fruit shelf life and yield in crossbreeding of Sletr1-2 mutant with Indonesian tropical tomatoes: Combining Ability of Sletr1-2 mutant - Gungun Wiguna; Farida Damayanti; Syariful Mubarok; Hiroshi Ezura; Anas ANAS (Biodiversitas Journal of Biological Diversity, 2021)
Postharvest losses are a significant concern for tomato breeding associated with their short fruit shelf life. Sletr1-2 is a new ethylene receptor mutant that has a prominent character in a prolonged fruit shelf life. This research aimed to estimate the combining ability of Sletr1-2 mutant and determine the selection method for future breeding associated with the fruit shelf-life and yield. Four lines of tropical tomato, i.e., 'Intan,' 'Mirah,' 'Ratna' and 'Mutiara,' were crossed with the wild type Micro-Tom (WT-MT) and Sletr1-2 mutant tomato using a line x tester mating design. A randomized complete block design with four replications was used to evaluate twelve F1 and their parents. The study revealed significant differences in the GCA of the line and tester but not for SCA. The lines and testers contributed more to total variance than their interaction. 'Intan' and Sletr1-2 mutants had the greatest fruit shelf-life combiners, with additive gene action being the most prevalent. Simple phenotypic selection or pure line selection from selected crosses in advanced generations would be preferable. 'Mutiara' was the best combiner for yield and plant growth, with non-additive gene action was the most common. The breeding strategy that considered dominance, overdominance, and epistasis was preferred.